2008
DOI: 10.1167/iovs.07-1156
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Glaucoma after Pediatric Cataract Surgery

Abstract: The risk of glaucoma after surgery for pediatric cataract is substantial and particularly high for those below 9 months of age at the time of surgery. Because the increased risk persists for many years after surgery, careful continuous monitoring for glaucoma is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 41 publications
1
64
1
7
Order By: Relevance
“…21 Our results are similar to those suggested by Rabiah 13 and Haargaard et al, 22 who suggested that the risk of glaucoma was higher in children operated before 9 months of age.…”
Section: Discussionsupporting
confidence: 91%
“…21 Our results are similar to those suggested by Rabiah 13 and Haargaard et al, 22 who suggested that the risk of glaucoma was higher in children operated before 9 months of age.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Oranlar arasındaki bu farklılık çalışmaya dahil edilen hasta gruplarının yaş ve takip sürelerinin farklı olmasına, tanı kriterlerine, katarakt dışı oküler ve sistemik anomalili hastaların çalışmaya dahil edilip edilmemesine ve cerrahi teknik farklılıklarına bağlı olabilmektedir. Ayrıca hastaların genellikle asemptomatik oluşu, göz içi basıncının ölçümü ve diğer muayenelerdeki zorluklar tanı koymayı güçleştirmektedir.…”
Section: Discussionunclassified
“…3,5,18 Takip süresi uzadıkça ortalama cerrahi -glokom intervali de uzamaktadır ve risk yaşam boyu devam etmektedir. Çalışmamızda da primer cerrahi -glokom intervali ortalama 47,3±23,3 ay (20 ay-7 yıl) olarak saptanmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations